Conceptualizing gambling disorder with the process model of emotion regulation - Rogier, Guyonne (J Behav Addict, 2018)
INTRODUCTION: Nowadays, gambling disorder (GD) is a worldwide health issue and there is a growing need to both improve our understanding of this disorder and to tailor specific interventions for its treatment. Moreover, theoretical models and preliminary empirical results suggest that difficulty in regulating emotional states might be involved in GD. However, literature describing clinical and theoretical aspects of emotional dysregulation among pathological gamblers (PGs) shows a lack of systematic description. OBJECTIVES: We aimed to provide, within an exhaustive theoretical framework of emotion regulation (ER) processing, empirical evidence supporting a conceptual model of GD as an ER affliction. METHODS: We commented on empirical evidence on the relationship between ER and GD in the light of two main conceptual models of emotion (dys)regulation. RESULTS: The results suggest there are actual deficits of ER processing among PGs, manifesting themselves through different ways and in different steps of the ER timeline. In addition, dysregulation of positive emotions may play a central role in GD. From a clinical point of view, we pointed out that deficits in ER might be multiple in nature and an assessment for GD should be accurate to identify the specific components accounting for the development and maintenance of the disorder. It should also orientate the clinician in selecting therapeutic objectives. CONCLUSIONS: The nature of emotional states that are difficult to regulate might account for the GD severity and indicate the subtype of PGs the patient belongs to. Treatment programs should be tailored on the specificity of PGs.